Insights into N-doping in single-walled carbon nanotubes for enhanced activation of superoxides: a mechanistic study. Issue 83 (18th August 2015) - Duan, Xiaoguang; Ao, Zhimin; Sun, Hongqi; Zhou, Li; Wang, Guoxiu; Wang, Shaobin
Abstract : Nitrogen-doped SWCNTs with enhanced carbocatalysis were investigated in the activation of superoxides by advanced oxidation and theoretical calculations. Abstract : Emerging characteristics upon nitrogen-doping were differentiated in the activation of superoxides over single-walled carbon nanotubes. Both experimental and theoretical studies revealed that enhanced peroxymonosulfate (PMS) activation is ascribed to a nonradical process while persulfate (PS) activation is accelerated via directly oxidizing water, yet hydrogen peroxide (H2 O2 ) activation is inert to N-doping. This study details the first insights into versatile N-doping in carbocatalysis for organic oxidation in sustainable remediation.